Making sense of penal difference: Political cultures and comparative penology - Brangan, Louise (Punishment & society, 2023)
In this paper I argue that if we are to make sense of why punishment differs between jurisdictions, then we should focus on the political cultures that shape penal practices. Political culture is conceived of here as a ‘practical consciousness’, made up of implicit and express cultural values and political commitments. Using the comparative case studies of Ireland and Scotland (from 1970–1990s), the paper tries to show that by taking the time to recover and interpret the beliefs and ideas that frame penal policymaking, we will be better able to illuminate and make sense of cross-national penal patterns. And using the leverage of cross-national contrast and analysis, we can also better understand punishment and its place in each society.